The relationship of synonasal symptoms with systemic and local markers of inflammation in children with bronchial asthma and allergic rhinitis - K. V. Gorbunova; S. V. Krasilnikova; T. I. Eliseeva; D. Yu. Ovsyannikov; A. V. Shakhov; O. V. Khaletskaya (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.